Novel insights on the relationship between T-tubular defects and contractile dysfunction in a mouse model of hypertrophic cardiomyopathy. (February 2016) - Crocini, C.; Ferrantini, C.; Scardigli, M.; Coppini, R.; Mazzoni, L.; Lazzeri, E.; Pioner, J.M.; Scellini, B.; Guo, A.; Song, L.S.; Yan, P.; Loew, L.M.; et al.
Abstract: Abnormalities of cardiomyocyte Ca 2 + homeostasis and excitation–contraction (E–C) coupling are early events in the pathogenesis of hypertrophic cardiomyopathy (HCM) and concomitant determinants of the diastolic dysfunction and arrhythmias typical of the disease. T-tubule remodelling has been reported to occur in HCM but little is known about its role in the E–C coupling alterations of HCM. Here, the role of T-tubule remodelling in the electro-mechanical dysfunction associated to HCM is investigated in the Δ160E cTnT mouse model that expresses a clinically-relevant HCM mutation. Contractile function of intact ventricular trabeculae is assessed in Δ160E mice and wild-type siblings. As compared with wild-type, Δ160E trabeculae show prolonged kinetics of force development and relaxation, blunted force-frequency response with reduced active tension at high stimulation frequency, and increased occurrence of spontaneous contractions. Consistently, prolonged Ca 2 + transient in terms of rise and duration are also observed in Δ160E trabeculae and isolated cardiomyocytes. Confocal imaging in cells isolated from Δ160E mice reveals significant, though modest, remodelling of T-tubular architecture. A two-photon random access microscope is employed to dissect the spatio-temporal relationship between T-tubular electrical activity and local Ca 2 + release in isolated cardiomyocytes. In Δ160E cardiomyocytes, a significant number of T-tubules (> 20%) fails to propagate action potentials, with consequent delay of local Ca 2 + release. At variance with wild-type, we also observe significantly increased variability of local Ca 2 + transient rise as well as higher Ca 2 + -spark frequency. Although T-tubule structural remodelling in Δ160E myocytes is modest, T-tubule functional defects determine non-homogeneous Ca 2 + release and delayed myofilament activation that significantly contribute to mechanical dysfunction. Highlights: Contraction and Ca 2 + transient kinetics are impaired in myocardial preparations from mice carrying the cardiac troponin T ∆ 160E mutation. T-tubules architecture is mildly altered in ∆160E cardiomyocytes. 20% of T-tubules fail to propagate action potential and produce delay of local Ca 2 + rise. Higher spatio-temporal variability of local Ca 2 + rise and increased Ca 2 + sparks frequency are found in ∆160E cardiomyocytes.